How to prove if a function is bijective?

The way to verify something like that is to check the definitions one by one and see if $g(x)$ satisfies the needed properties.

Recall that $F\colon A\to B$ is a bijection if and only if $F$ is:

  1. injective: $F(x)=F(y)\implies x=y$, and
  2. surjective: for all $b\in B$ there is some $a\in A$ such that $F(a)=b$.

Assuming that $R$ stands for the real numbers, we check.

Is $g$ injective?

Take $x,y\in R$ and assume that $g(x)=g(y)$. Therefore $2f(x)+3=2f(y)+3$. We can cancel out the $3$ and divide by $2$, then we get $f(x)=f(y)$. Since $f$ is a bijection, then it is injective, and we have that $x=y$.

Is $g$ surjective?

Take some $y\in R$, we want to show that $y=g(x)$ that is, $y=2f(x)+3$. Subtract $3$ and divide by $2$, again we have $\frac{y-3}2=f(x)$. As before, if $f$ was surjective then we are about done, simply denote $w=\frac{y-3}2$, since $f$ is surjective there is some $x$ such that $f(x)=w$. Show now that $g(x)=y$ as wanted.


Alternatively, you can use theorems. What sort of theorems? The composition of bijections is a bijection. If $f$ is a bijection, show that $h_1(x)=2x$ is a bijection, and show that $h_2(x)=x+2$ is also a bijection. Now we have that $g=h_2\circ h_1\circ f$ and is therefore a bijection.

Of course this is again under the assumption that $f$ is a bijection.


First show that $g$ is injective ($1$-$1$) by showing that if $g(x)=g(y)$, then $x=y$. This isn’t hard: if $g(x)=g(y)$, then $2f(x)+3=2f(y)+3$, so by elementary algebra $f(x)=f(y)$. By hypothesis $f$ is a bijection and therefore injective, so $x=y$.

Now show that $g$ is surjective. To do this, you must show that for each $y\in\Bbb R$ there is some $x\in\Bbb R$ such that $g(x)=y$. That requires finding an $x\in\Bbb R$ such that $2f(x)+3=y$ or, equivalently, such that $f(x)=\frac{y-3}2$. But $f$ is known to be a bijection and hence a surjection, so you know that there is such an $x\in\Bbb R$.

In general this is one of the two natural ways to show that a function is bijective: show directly that it’s both injective and surjective. The other is to construct its inverse explicitly, thereby showing that it has an inverse and hence that it must be a bijection. You could take that approach to this problem as well:

$$g^{-1}(y)=f^{-1}\left(\frac{y-3}2\right)\;,$$

since

$$\begin{align*} g\left(f^{-1}\left(\frac{y-3}2\right)\right)&=2f\left(f^{-1}\left(\frac{y-3}2\right)\right)+3\\ &=2\left(\frac{y-3}2\right)+3\\ &=y\;, \end{align*}$$

and since $f$ is a bijection, $f^{-1}\left(\frac{y-3}2\right)$ exists for every $y\in\Bbb R$.

Added: As Marc reminds me, this is only half the job: if you take this approach, you must either show directly that $g$ is injective, as I did above, or verify that the function that I called $g^{-1}$ above is a two-sided inverse, i.e., that $g^{-1}\big(g(x)\big)=x$ for $x\in\Bbb R$. This is not particularly difficult in this case:

$$\begin{align*} g^{-1}\big(g(x)\big)&=g^{-1}\big(2f(x)+3\big)\\ &=f^{-1}\left(\frac{\big(2f(x)+3\big)-3}2\right)\\ &=f^{-1}\big(f(x)\big)\\ &=x\;, \end{align*}$$

since $f$ is a bijection.


To prove a function is bijective, you need to prove that it is injective and also surjective.

"Injective" means no two elements in the domain of the function gets mapped to the same image.

"Surjective" means that any element in the range of the function is hit by the function.

Let us first prove that $g(x)$ is injective. If $g(x_1) = g(x_2)$, then we get that $2f(x_1) + 3 = 2f(x_2) +3 \implies f(x_1) = f(x_2)$. Since $f(x)$ is bijective, it is also injective and hence we get that $x_1 = x_2$.

Now let us prove that $g(x)$ is surjective. Consider $y \in \mathbb{R}$ and look at the number $\dfrac{y-3}2$. Since $f(x)$ is surjective, there exists $\hat{x}$ such that $f(\hat{x}) = \dfrac{y-3}2$. This means that $g(\hat{x}) = 2f(\hat{x}) +3 = y$. Hence, given any $y \in \mathbb{R}$, there exists $\hat{x} \in \mathbb{R}$ such that $g(\hat{x}) = y$. Hence, $g$ is also surjective.

Hence, $g(x)$ is bijective.

In general, if $g(x) = h(f(x))$ and if $f(x) : A \to B$ and $h(x): B \to C$ are both bijective then $g(x): A \to C$ is also bijective.

In your case, $f(x)$ was bijective from $\mathbb{R} \to \mathbb{R}$ and $h(x) = 2x+3$ is also bijective from $\mathbb{R} \to \mathbb{R}$.

Tags:

Functions